(untitled) (International Journal of Engineering and Computer Science, 2017)
Transformer supplied on 28/01/2011, erection completed on 03.10.2012, Oil filtration & circulation completed and pre commissioning test completed successfully. An oil sample is taken for BDV, PPM measurement& it came 82 KV &13PPM which was excellent for 132KVclass transformer. Transformer successfully charged on 0620 Hrs dt. 09.10.2012 & load increases gradually, when the transformer reaches on load of 41.2MW. It was observed thattransformer tripped on pressure relief device at 1358 Hrs on same date. .